A Systematic Review of Interventions for Hot and Cold Executive Functions in Children and Adolescents With Acquired Brain Injury. (21st March 2018) - Chavez-Arana, Clara; Catroppa, Cathy; Carranza-Escárcega, Edmundo; Godfrey, Celia; Yáñez-Téllez, Guillermina; Prieto-Corona, Belén; de León, Miguel A; Anderson, Vicki
Abstract: Objective: We investigated interventions, which aimed to improve cold and hot executive functions (EFs) in children and adolescents with a diagnosis of acquired brain injury (ABI). Methods: The following electronic databases were searched: Medline, CINAHL, PsycINFO, and Pubmed. The database filters limited the search to articles published between 1990 and July 2017 in English or Spanish, including children and adolescents. Articles were read and classified according to the levels of evidence of the Australian National Health and Medical Research Council and the Downs and Black checklist was used for Measuring Study Quality. Results: Thirty studies are reported in this systematic review. Level of evidence, quality of the studies, characteristics of the participants, interventions implemented, and outcomes are described. Conclusions: The study of rehabilitation for executive dysfunction in children with ABI is emerging. Although few high-quality intervention studies exist in this area, which limits conclusions regarding intervention efficacy, results of existing studies suggest that education for parents may be an important component of intervention. Moreover, caregiver involvement may improve the effectiveness of hot EFs rehabilitation interventions, while high intervention session frequency may be important in improving cold EFs. Positive behavior supports and specific training based on a cognitive model provided some promising findings, which require further evaluation.